Analysis of Dermatophytosis Therapy at Persian Cat After Using Apple Vinegar (Malus domestica) - Pratiwi, Rina Hidayati; Astiningrum, Rania Dwita; Yulistiana, Yulistiana (Media Kedokteran Hewan, 2022)
Dermatophytosis is a skin disease that mostly infects Persian cats caused by microorganisms, Microsoprum canis. Fungal diseases are often repeated on the surface of the cat's skin and the treatment is still using synthetic chemical-based drugs. Therefore, it is necessary to use a natural antifungal that is economically easy to obtain and can minimize side effects when the cat is undergoing treatment. The purpose of this study was to analyze the response of skin surface in Persian cats (Felis sp.) after using apple cider vinegar. The method used to analyze is a qualitative descriptive method with triangulation techniques. After analyzing the eradication of fungi in 4 samples of Persian cats (Felis sp.) through the use of apple cider vinegar, it was found that the use of apple cider vinegar can eradicate fungi in Persian cats. The cat that had been treated with apple cider vinegar experienced a very good change, where the cat was no longer scratching his body intensely because he felt very itchy caused by the fungus, and his body was clean and had no more fungal crusts. After the fungus is completely removed from the cat's body, the cat's hair will immediately grow by itself. The conclusion is apple cider vinegar can be used for dermatophytosis therapy systemic because it has the ability to inhibit pathogenic fungi activity.